DEVELOPING DIGITAL WORKSHEET BASED ON ANDROID SUBJECT BIODIVERSITY GASTROPODS IN MANGROVE FOREST AT TUNDA ISLAND BANTEN - Indria Wahyuni; Tatang Supandi; Bambang Ekanara (Universitas Sultan Ageng Tirtayasa, 2019)
ABSTRACTThis research aimed to develop a digital student’s work sheets used Android based on mangrove forest of Tunda Island gastropod diversity for invertebrate sub concept and to assessed the student’s work sheets based on material, media, and student response aspects. This research was a developments research (R&D) with 3-D (Define, Design, and Develop) design and supported by exploration of gastropod diversity in mangrove forest of Tunda Island at June 2017. The instruments in this research were interview and expert assessment sheets. The data from assesment sheets was analized from qualitative to be quantitative. The data from assessment sheets was used to improve the student’s worksheets contents and structures. The result of this research showed 20 species gastropods identified at mangrove forest of Tunda Island including 2 subclass, Pulmonata and Prosobranchia. The gastropod diversity index on Tunda Island was 1,2024, classified in the medium category. The result of exploration of gastropod diversity in Tunda Island also used as material content in student’s work sheets development. Based on experts assessment and student response, the average value of the student’s work sheet were 89% and 87,1% with category very good and feasible to use as a teaching learning materials for 10th grade of senior high school.Keywords: Android, Gastropods, Student’s Work Sheets, Tunda Island